2020
DOI: 10.1042/bsr20192384
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-140-5p ameliorates the high glucose-induced apoptosis and inflammation through suppressing TLR4/NF-κB signaling pathway in human renal tubular epithelial cells

Abstract: Hyperglycemia-induced renal tubular cell injury is thought to play a critical role in the pathogenesis of diabetic nephropathy (DN). However, the role of miRNAs in renal tubular cell injury remains to be fully elucidated. The aim of the present study was to investigate the role and mechanisms of miRNAs protecting against high glucose (HG)-induced apoptosis and inflammation in renal tubular cells. First, we analyzed microRNA (miRNA) expression profiles in kidney tissues from DN patients using miRNA microarray. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In our previous study, we found that miR-140-5p could alleviate cisplatin-induced oxidative stress by regulating the Nrf2/ARE signaling pathway (Liao et al, 2017). Additionally, in diabetic nephropathy, the expression of miR-140-5p in kidney tissues was significantly down-regulated, and miR-140-5p protected HK-2 cells from high glucose-induced injury by inhibiting the TLR4/NF-kappaB pathway (Su et al, 2020). Several studies suggested that miR-140-5p may be linked to fibrosis in some diseases.…”
Section: Introductionmentioning
confidence: 95%
“…In our previous study, we found that miR-140-5p could alleviate cisplatin-induced oxidative stress by regulating the Nrf2/ARE signaling pathway (Liao et al, 2017). Additionally, in diabetic nephropathy, the expression of miR-140-5p in kidney tissues was significantly down-regulated, and miR-140-5p protected HK-2 cells from high glucose-induced injury by inhibiting the TLR4/NF-kappaB pathway (Su et al, 2020). Several studies suggested that miR-140-5p may be linked to fibrosis in some diseases.…”
Section: Introductionmentioning
confidence: 95%
“…Diabetic nephropathy-related OxS is also improved upon elevation of miR-214 via using uncoupling protein 2 (UCP2) so as to affect signaling via ROS/AKT/mTOR pathway [274]. miR-140-5p also ameliorated HG-promoted ROS generation, inflammation, and apoptosis in human renal tubular epithelial cells (HK-2) via repressing signaling via TLR4/NF-κB [275]. ROS production along with apoptosis of HK-2 became potentiated upon HG-triggered upregulation of miR-125b, which directly targets a protective molecule, angiotensin-converting enzyme 2 (ACE2) [276].…”
Section: Mirnas In Mets-a Link With Obesity and Insulin Resistance/hymentioning
confidence: 99%
“…Chen et al analyzed 9 differentially expressed miRNAs in the renal tubular epithelial cell population of mice with fatal ischemia-induced acute kidney injury, in which miR-483 was significantly downregulated [30]. More importantly, Su et al analyzed miRNA expression profiles in kidney tissue of DN patients through miRNA microarray, and miR-483-5p was downregulated in the miRNAs [15]. Therefore, in this study, we first analyzed the expression levels of miR-483-5p in serums of different subjects and confirmed that miR-483-5p was significantly decreased in the serums of DN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have analyzed the differentially expressed miRNAs in peripheral blood of DN patients and healthy controls including miR-483-5p [15]. miR-483 is located on chromosome 11p15.5, and its level imbalance is involved in a variety of human diseases, including breast cancer, nasopharyngeal carcinoma, myocardial infarction, and systemic sclerosis [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%